2010
DOI: 10.4049/jimmunol.0904054
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Induced Apoptosis Leads to Active Suppression of Delayed-Type Hypersensitivity by CD8+ Regulatory T Cells through a TRAIL-Dependent Mechanism

Abstract: Patients who survive severe sepsis often display severely compromised immune function. One hallmark of such immune suppression in septic patients is an impaired delayed-type hypersensitivity (DTH) response, manifested by a loss of skin testing to recall Ags. Because sepsis induces significant apoptosis in lymphoid and myeloid cells, and apoptotic cells are themselves tolerogenic, we tested the hypothesis that suppression of DTH is mediated by tolerogenic properties of the apoptotic cells generated during sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 50 publications
7
69
0
3
Order By: Relevance
“…Additional evidence for the sepsis-associated immunosuppression is the high incidence of herpes virus reactivation that occurs in patients with prolonged septic episodes (5). These clinical observations are supported from in vitro data showing impaired cytotoxicity and increased apoptosis of immune effectors from septic patients (6).…”
Section: Pathogenesis Of Sepsissupporting
confidence: 71%
“…Additional evidence for the sepsis-associated immunosuppression is the high incidence of herpes virus reactivation that occurs in patients with prolonged septic episodes (5). These clinical observations are supported from in vitro data showing impaired cytotoxicity and increased apoptosis of immune effectors from septic patients (6).…”
Section: Pathogenesis Of Sepsissupporting
confidence: 71%
“…It is now well established that following an early cytokine storm, sepsis patients become severely immunosuppressed, which renders them susceptible to secondary nosocomial infections. Human and animal studies indicate that massive leukocyte apoptosis occurs in sepsis and suppresses immunity by triggering a tolerogenic program in antigen-presenting cells (2)(3)(4)(5)(6)(7)(8)(9)(10). As a result, sepsis patients have impaired delayed-type hypersensitivity (DTH) 7 and are often unable to mount an immune response to recall antigens (11,12).…”
Section: Hmgb1 With Potential Therapeutic Implications In Infectiousmentioning
confidence: 99%
“…Sepsis has traditionally been considered an excessive systemic inflammatory response to invading pathogens; however, several clinical trials have shown that suppression of inflammation has no effect on sepsis-induced AKI (6,7). Previous study demonstrated the occurrence of compensated anti-inflammatory response syndrome follows systemic inflammatory response syndrome (8), and according to recent observations, mortality from sepsis or sepsis-induced organ dysfunction might be associated with paradoxical immune suppression, characterized by unregulated apoptosis of immune cells (9)(10)(11)(12).…”
mentioning
confidence: 94%